Cyclicities and clusters in the lacustrine sequence of Heqing basin (SW China): Its use for dating and palaeoenvironmental reconstruction - Goddu, Srinivasa R; Hu, Shouyun; Appel, Erwin (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.145